Analisis Permasalahan Perkembangan Peserta Didik Tingkat Sekolah Dasar dan Solusinya - Dwi Aprina, Syalsa; Hafza, Abyena; Meida Sari, Putri; Ramadani, Novia; Handayani, Nofia (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2023)
Primary school children. that the characteristics of human development vary according to the factors that influence human development. The developmental characteristics of school-aged children are different from the developmental characteristics of adolescence and the developmental characteristics of adulthood. Development is influenced by many factors that cause problems in development. These factors include genetic factors and environmental factors. In developing these seven aspects, problems sometimes arise that can be corrected with the support of those closest to you, especially family. Everyone has their own strengths and weaknesses, so a child should not be forced to master all stages of development.